PREDICTING EXHAUST SOUND POWER LEVELS OF GENERAL PURPOSE BOILERS - Stevens, Robert D; Gastmeier, William J (Canadian Acoustics, 2016)
This presentation introduces a new prediction equation derived empirically from sound power measurements of various boiler exhausts, conducted by the authors between 2003 and 2015, with thermal ratings ranging from about 500 kW to 50 MW. The new equation is shown to agree well with the measured data for boiler exhausts, suggesting that it is a suitable estimate when measured data are unavailable.